Analysis of Arabic Language Learning Difficulties of Grade VII Students of Madrasah Miftahul' Ulum Dolok Masihul in Mastering Arabic Vocabulary - Khairul Jamil; Khumairani Putri (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to find and describe students' difficulties in learning Arabic. This type of research is qualitative research using the pictorial media method. And Arabic language skills, especially mastery of Arabic vocabulary (mufradat) is very important to master, and the results of the study show that first, the lack of student interest and motivation to learn Arabic, second, the difficulty of students reading and understanding the meaning of each Arabic vocabulary, third, the lack of parental concern for student Arabic learning outcomes, fourth, the method of delivering material by monotonous teachers using the lecture method, and finally, the use of less productive learning media.